Functionalized Hydrogel-Based Wearable Gas and Humidity Sensors - Luo, Yibing; Li, Jianye; Ding, Qiongling; Wang, Hao; Liu, Chuan; Wu, Jin (Nano-Micro Letters, 2023)
Breathing is an inherent human activity; however, the composition of the air we inhale and gas exhale remains unknown to us. To address this, wearable vapor sensors can help people monitor air composition in real time to avoid underlying risks, and for the early detection and treatment of diseases for home healthcare. Hydrogels with three-dimensional polymer networks and large amounts of water molecules are naturally flexible and stretchable. Functionalized hydrogels are intrinsically conductive, self-healing, self-adhesive, biocompatible, and room-temperature sensitive. Compared with traditional rigid vapor sensors, hydrogel-based gas and humidity sensors can directly fit human skin or clothing, and are more suitable for real-time monitoring of personal health and safety. In this review, current studies on hydrogel-based vapor sensors are investigated. The required properties and optimization methods of wearable hydrogel-based sensors are introduced. Subsequently, existing reports on the response mechanisms of hydrogel-based gas and humidity sensors are summarized. Related works on hydrogel-based vapor sensors for their application in personal health and safety monitoring are presented. Moreover, the potential of hydrogels in the field of vapor sensing is elucidated. Finally, the current research status, challenges, and future trends of hydrogel gas/humidity sensing are discussed. Highlights: 1 A systematic summary of the research progress of hydrogel-based gas and humidity sensors is presented. 2 The sensing mechanism of hydrogel-based gas and humidity sensors is elaborated. 3 The potential of hydrogel-based vapor sensors in different fields of application is demonstrated.